Sosialisasi Terkait Fungsi Peran Manajemen, Perbaikan Gizi Dalam Menjaga Kesehatan Lutut Dan Sendi Kalangan Dewasa Dan Lansia Di Kelurahan Gayamsari Kecamatan Gayamsari - Wahyu Puspitasari; Metta Christiana; Shinta Eka Kartika; Risqotul Adidatul Izzah; Sinta Aprilia Wahyuningsih (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
It turns out that not all people who live in the Gayamsari Village Office, Gayamsari District, Semarang City understand the importance of knee and calf health and the dangers faced by patients or sufferers. Residents of Gayamsari Village, Gayamsari District, Semarang City initially only knew about osteoporosis and its dangers and prevention, but they did not know about sarcopenia, its dangers and its prevention or treatment.According to Wiyashihat, sarcopenia syndrome in 2023 which is characterized by progressive loss of skeletal muscle mass and strength is a syndrome characterized by a decrease in quality of life, an increased risk of falling and even death. Specifically, sarcopenia is muscle wasting that can interfere with regular daily activities. With the weaknesses and dangers of sarcopenia, it is hoped that the public will not underestimate it, be more careful and prevent rather than cure, therefore our PKM team, Faculty of Economics, University of Semarang, consists of three lecturers. in various fields under the Faculty of Economics assisted by two S1 accounting students from the University of Semarang who are eager to conduct outreach to educate about the basics of sarcopenia and its dangers. and how to prevent it.The community service organized by our group on Saturday 24 July 2023 which starts at 06:00 WIB - 08:15 WIB will be held at the Gayamsari Village Office, Gayamsari District, Semarang City. lecturer in the field. The Faculty of Economics explained the importance of nutrition, the event was attended by 45 participants from adults to the elderly, Kelurahan staff representing the Lurah were present because they were sad because their mother had died in Rahmatullah. The results of this activity were successful, the community was very enthusiastic, they enjoyed participating in the event, they also played an active role in organizing this event and the advice given, if an event like this was held they were happy. to participate. in the next event, with material or topics that are more interesting in the future.